2011
DOI: 10.1890/11-0599.1
|View full text |Cite
|
Sign up to set email alerts
|

Defining conservation priorities for freshwater fishes according to taxonomic, functional, and phylogenetic diversity

Abstract: To date, the predominant use of systematic conservation planning has been to evaluate and conserve areas of high terrestrial biodiversity. Although studies in freshwater ecosystems have received recent attention, research has rarely considered the potential trade‐offs between protecting different dimensions of biodiversity and the ecological processes that maintain diversity. We provide the first systematic prioritization for freshwaters (focusing on the highly threatened and globally distinct fish fauna of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
145
0
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(154 citation statements)
references
References 52 publications
3
145
0
6
Order By: Relevance
“…1. of biodiversity has been observed globally for birds (26), freshwater fishes (22), and mammals (15). Such lack of congruence triggers a conservation conflict, because conservation strategies based only on taxonomic diversity do not include important phylogenetic and functional hotspots (15,26).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1. of biodiversity has been observed globally for birds (26), freshwater fishes (22), and mammals (15). Such lack of congruence triggers a conservation conflict, because conservation strategies based only on taxonomic diversity do not include important phylogenetic and functional hotspots (15,26).…”
Section: Resultsmentioning
confidence: 99%
“…We found that removing traits that had high proportions of missing data before imputations did not change our main results. To represent the trait dimension in the prioritization analyses, we followed the framework of Strecker et al (22), using a grid cells × traits matrix. To create this matrix, all trait variables were converted into binary format.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As result, researchers tend to focus on different aspects of biodiversity such as 83 taxonomic, phylogenetic, and functional diversity (Swenson, 2011). Each of these aspects of biodiversity 84 may vary differently among regions and taxa, and each must therefore be assessed by independent criteria 85 (Strecker et al, 2011). 86 …”
mentioning
confidence: 99%